Colorful gratitude: INFORMS hi-tea celebration in blue and red / Dr. Hajah Imilia Ibrahim and Sabariah Abd Samad - Ibrahim, Imilia; Abd Samad, Sabariah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The School of Information Science UiTM Sarawak supervises the Information Management Diploma Dean's Appreciation and Award Ceremony, an event organized by the Information Management Association (INFORMS). This occasion is organized to honor the students and committee members of the Diploma in Information Management who achieved outstanding results on the most recent examination and those who have served and represented the faculty in various campus and university-level activities. After a single day of conduct, the event concluded on Saturday afternoon, January 6, 2024. Students commenced their presence in the Banquet Hall of the Penview Hotel in Kuching at 1:30 p.m. on that fateful Saturday, anticipating directives from the INFORMS committee prior to the commencement of the program. The lecturers from the School of Information Science and the Head of Study Center, led by Dr. Susan Hydra Sikayu, arrived precisely at 2:00 p.m.